A five-year Experience in Using the Extended Cone Technique - Hiram Rodríguez Blanco; Pedro Rolando López Rodríguez; Juan Ramón Cruz Alonso; Luis Enrique Pampin Camejo; Jorge Satorre Rocha; Olga León González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Background: the use of meshes for hernia repair reached its greatest popularity in the 1980´s. In 2007, a new mesh placement technique was designed in the Multiprofile Clinic in Luanda, Angola, which meets all the requirements of hernia surgery, consisting in the occlusion of the hernia ring and reinforcement of the canal wall. In 2009 this procedure was introduced into the Enrique Cabrera Hospital in Havana. Objective: to show the results of the extended cone technique in the treatment of inguinal hernia in the Enrique Cabrera Teaching Hospital. Methods: a case series study was conducted in 100 patients in whom 110 hernias were operated using a prosthetic technique called extended cone, at the Enrique Cabrera Hospital in Havana between 2009 and 2013. Gilbert's classification modified by Robbin and Rutkow was applied. The variables analyzed were age, sex, location of the hernia, type of hernia according to Gilbert's classification, complications and recurrence rate. Results: male patients predominated. The most frequent location was the left inguinal region. Type III hernias according to Gilbert's classification were the most common. There were 15 minor complications and there have been no recurrences thus far. Conclusions: the proposed technique is a safe procedure and another option for the treatment of patients with type III, IV and VI hernias according to Gilbert's classification modified by Rutkow and Robbins.